2013
DOI: 10.1364/oe.21.019922
|View full text |Cite
|
Sign up to set email alerts
|

Projection angle dependence in grating-based X-ray dark-field imaging of ordered structures

Abstract: Abstract:Over the recent years X-ray differential phase-contrast imaging was developed for the hard X-ray regime as produced from laboratory X-ray sources. The technique uses a grating-based Talbot-Lau interferometer and was shown to yield image contrast gain, which makes it very interesting to the fields of medical imaging and non-destructive testing, respectively. In addition to X-ray attenuation contrast, the differential phase-contrast and dark-field images provide different structural information about a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 16 publications
(24 reference statements)
1
34
0
Order By: Relevance
“…These techniques have evolved in different ways: X-ray tensor tomography has evolved from X-ray parallel perpendicular 50 mm 50 mm dark-field imaging using a grating interferometer [164], where ultra-small X-ray scattering is exploited [165]. The intensity modulations due to the rotation of the third grating [166,167] or of the sample [168,169] reveal the 2D orientation of the ultrastructure, and have been used to retrieve 2D ultrastructure organization of bone [170] or dentin [166]. By rotating the sample around two axes, and using an iterative reconstruction algorithm, it is possible to retrieve the 3D ultrastructure orientation [161].…”
Section: X-ray Scattering/diffraction Tensor Tomographymentioning
confidence: 99%
“…These techniques have evolved in different ways: X-ray tensor tomography has evolved from X-ray parallel perpendicular 50 mm 50 mm dark-field imaging using a grating interferometer [164], where ultra-small X-ray scattering is exploited [165]. The intensity modulations due to the rotation of the third grating [166,167] or of the sample [168,169] reveal the 2D orientation of the ultrastructure, and have been used to retrieve 2D ultrastructure organization of bone [170] or dentin [166]. By rotating the sample around two axes, and using an iterative reconstruction algorithm, it is possible to retrieve the 3D ultrastructure orientation [161].…”
Section: X-ray Scattering/diffraction Tensor Tomographymentioning
confidence: 99%
“…Thus, scattering and phase shifts along the direction of the grating lines have no influence on the contrast of the Talbot pattern. The directional dependence of the dark-field image holds the capability of retrieving information about the angular variations of the local scattering power of a sample [12,14]. For that purpose, the object is rotated around the beam axis and at least three images at different angular orientations of the object are acquired.…”
Section: Directional X-ray Dark-field Imagingmentioning
confidence: 99%
“…The dark-field signal is mainly based on small angle X-ray scattering (SAXS) caused by variations in the electron density of an inhomogeneous sample [10,11]. As a further analysis tool, directional X-ray dark-field imaging is used in order to reconstruct fibre orientations of micrometer-sized aligned structures which are not resolvable directly [12][13][14]. The method is applicable for the analysis of bones [15][16][17] or the characterisation of fibre alignments in polymers [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The dark-field image is thus an image of the granularity or fibrousness of the sample. It was shown that biological, human and inanimate objects with different microstructural properties can produce contrasts in the dark-field image [9][10][11]. This information on the microstructure of the sample, not necessarily accessible with standard radiography, is of special interest for an eventual application in medical imaging [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%